A CORPUS-BASED ANALYSIS OF DISCOURSE STRATEGIES USED BY PRIMARYINCLUSIVE SCHOOLS - Sofi Yunianti; Idhoofiyatul Fatin; Ahmad Mahmudi (Journal of Advances in Linguistics and English Teaching (JALET), 2025)
Teachers and students’ interactions play a crucial role in achieving learning outcomes. Therefore, this study aims to find out how discourse strategies are used in a primary inclusive school. Through the participation of a primary inclusive school’s teacher, a corpus of recorded data was constructed. The discourse strategies were then identified and categorized based on the theory of Dornyei and Scott. The result of the study revealed that, based on corpus-analysis, the teacher used only the More Communicative Potential strategy. Within this category, the most frequently used strategy was a comprehension check. This was primarily applied because the teacher’s main purpose was to deliver the lesson clearly and coherently while ensuring students understood the material. This study implied that it is essential for teachers to be aware of and apply appropriate discourse strategies to support effective classroom interaction.